k-semistratifiable spaces and expansions of set-valued mappings - Peng-Fei Yan; Xing-Yu Hu; Li-Hong Xie (Applied General Topology, 2018)
In this paper, the concept of k-upper semi-continuous set-valued mappings is introduced. Using this concept, we give characterizations of k-semistratifiable and k-MCM spaces, which answers a question posed by Xie and Yan.